2021
DOI: 10.1016/j.meatsci.2020.108277
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and microbiological characteristics of El-Guedid from meat of different animal species

Abstract: El-Guedid is an Algerian traditional meat-based product that is prepared from red meats. It belongs to the wide diversity of salted/dried meat products. This study described the physicochemical and microbiological properties of different products from four animal origins and during all the conservation. Results indicated that these products were mainly characterized by a low moisture with an average decrease of water content between 15.6% and 16.3% for all the samples, and a decrease in water activity ranging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 57 publications
(76 reference statements)
2
12
1
Order By: Relevance
“…Aerococcus and Enterococcus species isolated from el-guedid have exhibited a probiotic potential [ 43 ]. Bader et al (2021) reported the results of a more comprehensive study of el-guided physicochemical and microbiological properties, considering the type of raw red meat and the conservation time [ 44 ]. Lactic acid bacteria and coagulase-negative staphylococci were the dominant populations in el-guedid , including Leuconostoc mesenteroides , Lactobacillus sakei , and Staphylococcus saprophyticus .…”
Section: Resultsmentioning
confidence: 99%
“…Aerococcus and Enterococcus species isolated from el-guedid have exhibited a probiotic potential [ 43 ]. Bader et al (2021) reported the results of a more comprehensive study of el-guided physicochemical and microbiological properties, considering the type of raw red meat and the conservation time [ 44 ]. Lactic acid bacteria and coagulase-negative staphylococci were the dominant populations in el-guedid , including Leuconostoc mesenteroides , Lactobacillus sakei , and Staphylococcus saprophyticus .…”
Section: Resultsmentioning
confidence: 99%
“…The dominance of L. sakei and S. xylosus was observed in most products. Among LAB beyond the commonly occurring species of lactobacilli, L. sakei, L. curvatus and L. plantarum, other species of lactobacilli, Enterococcus, Leuconostoc, Pediococcus, Lactococcus, Tetragenococcus and Weissella species were identified [18,58,59,60,61]. P. pentosaceus was dominant in Salame Piemonte, as shown by metataxonomic analysis [61].…”
Section: Figurementioning
confidence: 90%
“…An example is El-Guedid, also called «el khlî», a traditional processed meat product in Algeria made from sheep, beef, goat and camel meat cut into strips, seasoned abundantly with salt and spices and exposed to the open air under the sun from one to several weeks until reaching aw 0.625 and pH 5.2-5.5. Finally, it is stored in jars for up to one year [18]. Other not stuffed dry fermented meats are the Algerian Kaddid [19], beef jerky [20], Biltong in South Africa, that has also smoked versions [21], Kilishi, a jerky type RTE sun dried meat product popular in Northern Cameroon and Nigeria [22,23], Kitoza from Madagascar [24], Socol and Charqui in South America [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Other than that, the microbiological properties of El-Guedid, a traditional dried meat product from Algerian, were studied to describe its differences in microbiological properties as it was harbored from different origins and downstream processes ( 92 ). The results have observed that, the samples were categorized by reduced moisture content (15.6–16.3%) and a w values (0.66–0.68), as well as the salt content ranging between 8.8 and 19.3% and oscillated pH values from 6.4–6.4 to 5.2–5.5.…”
Section: Microbiological Characteristics Of Dried Meatmentioning
confidence: 99%